The impact of specialised gastroenterology services for pelvic radiation disease (PRD): Results from the prospective multi-centre EAGLE study - John N. Staffurth; Stephanie Sivell; Elin Baddeley; Sam Ahmedzai; H. Jervoise Andreyev; Susan Campbell; Damian J. J. Farnell; Catherine Ferguson; John Green; Ann Muls; Raymond O’Shea; Sara Pickett; et al. (PLoS ONE, 2025)
To undertake a mixed-methodology implementation study to improve the well-being of men with gastrointestinal late effects following radical radiotherapy for prostate cancer. All men completed a validated screening tool for late bowel effects (ALERT-B) and the Gastrointestinal Symptom Rating Score (GSRS); men with a positive score on ALERT-B were offered management following a peer reviewed algorithm for pelvic radiation disease (PRD). Health-related quality of life (HRQoL) at baseline, 6 and 12 months; and healthcare resource usage (HRU) and patient, support-giver, staff experience and acceptability of staff training (qualitative analysis) were assessed. Two nurse- and one doctor-led gastroenterology services were set up in three UK cancer centres. Men (n = 339) who had had radical radiotherapy for prostate cancer at least 6 months previously, were recruited; of which 91/339 were eligible to participate; 58/91 men (63.7%) accepted the referral. Diagnoses included: radiation proctopathy (n = 18); bile acid malabsorption (n = 15); fructose or lactose intolerance and/or small intestinal bacterial overgrowth (n = 20); vitamin B12/D deficiency (n = 20). Increases in quality of life, sexual activity and/or sexual function, and decrease in specific symptoms (e.g. bowel-related or urinary) between 6 and 12 months were observed. Limited HRU modelling suggested staff costs were £117-£185, depending on the service model; total costs averaged £2,243 per patient. Both staff and patients welcomed the new service although there was concern about long-term funding and sustainability beyond the timeframe of the study (qualitative). PRD is increasingly recognised worldwide as an ongoing consequence of curative pelvic radiotherapy, despite widespread implementation of advanced radiotherapy techniques. Specialised services following national guidelines are required.